Genomic characterization of multidrug-resistant Salmonella serovars Derby and Rissen from the pig value chain in Vietnam - González Santamarina, B.; García-Soto, S.; Sinh Dang-Xuan; Abdel-Glil, M.Y.; Meemken, D.; Fries, R.; Tomaso, H. (Frontiers Media, 2021)
Nontyphoidal Salmonella (NTS) is the most reported cause of bacterial foodborne zoonoses in Vietnam, and contaminated pork is one of the main sources of human infection. In recent years, the prevalence of NTS carrying multiple antimicrobial resistance genes (ARGs) have been increased. The genomic characterization along the pig value chain and the identification of ARGs and plasmids have the potential to improve food safety by understanding the dissemination of ARGs from the farm to the table. We report an analysis of 13 S. Derby and 10 S. Rissen isolates, collected in 2013 at different stages in Vietnamese slaughterhouses and markets. VITEK 2 Compact System was used to characterize the phenotypical antimicrobial resistance of the isolates. In addition, whole-genome sequencing (WGS) was used to detect ARGs and plasmids conferring multidrug resistance. Whole genome single nucleotide polymorphism typing was used to determine the genetic diversity of the strains and the spread of ARGs along the pig value chain. Altogether, 86.9% (20/23) of the samples were resistant to at least one antibiotic. Resistance to ampicillin was most frequently detected (73.9%), followed by piperacillin and moxifloxacin (both 69.6%). At least one ARG was found in all strains, and 69.6% (16/23) were multidrug-resistant (MDR). The observed phenotype and genotype of antimicrobial resistance were not always concordant. Plasmid replicons were found in almost all strains [95.6% (22/23)], and the phylogenetic analysis detected nine clusters (S. Derby, n = 5; S. Rissen, n = 4). ARGs and plasmid content were almost identical within clusters. We found six MDR IncHI1s with identical plasmid sequence type in strains of different genetic clusters at the slaughterhouse and the market. In conclusion, high rates of multidrug resistance were observed in Salmonella strains from Vietnam in 2013. Genomic analysis revealed many resistance genes and plasmids, which have the potential to spread along the pig value chain from the slaughterhouse to the market. This study pointed out that bioinformatics analyses of WGS data are essential to detect, trace back, and control the MDR strains along the pig value chain. Further studies are necessary to assess the more recent MDR Salmonella strains spreading in Vietnam.